Are there sex differences in muscle coordination of the upper girdle during a sustained motor task?. (April 2019) - Cid, Marina Machado; Oliveira, Ana Beatriz; Januario, Leticia Bergamin; Côté, Julie N.; de Fátima Carreira Moreira, Roberta; Madeleine, Pascal
Abstract: Purpose: The higher prevalence of work-related musculoskeletal disorders among women compared with men could be explained by sex-gender differences related to biological and physiological processes. The aim of this study was to evaluate sex differences in motor coordination during a sustained and repetitive motor task. Methods: Seventeen healthy females and 21 healthy males participated. The surface electromyography (sEMG) of the trapezius portions and serratus anterior were recorded. Root mean square (RMS) values were computed to assess the level of muscle activity. The standard deviation (SD) and coefficient of variation (CV) were computed as metrics of size of variability. The normalized mutual information (NMI) values were calculated as index of functional connectivity between muscles pairs. Results: Females had higher normalized RMS values for the upper trapezius (acromial fibers) and serratus anterior muscles compared with males. RMS decreased, SD and CV increased while NMI decreased for almost all muscle pairs over time. Conclusion: The present work showed some signs of sex differences in muscle coordination of the shoulder girdle during a sustained motor task, performed with the upper limb positioned below of the shoulder level.